Teaching Reported Speech - Regmi, Dan Raj (Journal of NELTA, 2010)
The main purpose of this paper is to analyze the major errors in reported speech made by the learners of Grade XII of Management stream and put forward some practical suggestions for the remedies of those errors. There are a few contributions made by the teachers as well as others interested in teaching reported speech in English to the students speaking languages other than English. Sharma (2002) deals with teaching reported speech in English, which is important for building insights on how effectively we can help the students speaking Nepali master the structural patterns of reported speech in English. Key words: reported speech, tstructures, grammatical items DOI: 10.3126/nelta.v14i1.3101 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 132-137